The Influence of Role Stressor on Negative Affect with Proactive Personality as a Moderating Variable in Civil Servants after Bureaucratic Simplification in Regional Government “X” - Setyawan, Agung; Wahyuni, Purbudi; Ambarwati, Sri Dwi Ari (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study investigated the effects of role stressors consisting of role conflict, role ambiguity, and role overload on negative affect among civil servants in Local Government “X” after bureaucratic simplification and role equalization. The study further explored the moderating role of proactive personality in this relationship. A survey of 70 civil servants, selected using proportional stratified random sampling, provided the primary data, which were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results revealed that all three role stressors significantly contributed to negative affect. Proactive personality showed a significant positive moderating effect on the relationship between role overload and negative affect (β = 0.122, p < 0.05), indicating that proactive individuals may experience increased negative emotions when faced with excessive workload. However, proactive personality did not moderate the effects of role conflict and role ambiguity on negative affect. These findings underscore the need for targeted interventions to address workload-related stress in bureaucratic transformation.